Vitamin C and viral infection - Aris Wibudi (Indonesian Nutrition Association, 2020)
Micronutrients such as vitamins, minerals and trace elements influence various metabolic processes that are directly associated with immune functions, especially vitamin C and D. The adequacy of vitamin C in leukocytes plays a major role in the success of immune response, both innate and adaptive. The highest vitamin C concentrations were found in lymphocytes, monocytes, platelets and neutrophils respectively.